Sade, les femmes et le féminisme dans les années 1950 - Perrine Coudurier (Itinéraires)
This paper is a study of the relationships between Sade and his posterity in the Fifties, in France, around the representation of women being. Simone de Beauvoir and Pauline Réage are two authoresses who make Sade an important thinker of the female condition. Between fascination, submission and rebellion, they explain the difficult position of the women both in literature and in society. It seems to be difficult, for Sade and these two authoresses, to avoid a mythic image of women and to escape the binarity man/woman.